Partial Amino Acid Metabolism and Glutamine Synthesis as the Ammonia Defensive Strategies During Aerial Exposure in Chinese Loach Paramisgurnus dabryanus - Zhang, Yun-Long; Wang, Guang-Yi; Zhang, Zi-Han; Xie, Yun-Yi; Jin, Hui; Dong, Zhao-Ran (Frontiers in Physiology, 2019)
The Paramisgurnus dabryanus was exposed to air to assessing the changes of plasma, liver and muscle free amino acid contents. The free amino acid concentrations in plasma, liver and muscle of P. dabryanus were significantly affected by aerial exposure (P<0.05). After 12 h of aerial exposure, the plasma glutamate contents increased significantly (P<0.05) and reached peak value at 24 h of air exposure. With the increasing of air exposure time, the plasma alanine contents increased significantly and dramatically higher than the control values (P<0.05). From 24 h to 48 h of aerial exposure, the liver free glutamate contents increased significantly and reached the peak value at 48 h of air exposure (P<0.05). The liver free alanine contents in air exposure group were markedly higher than this values in control group (P<0.05). After 72 h of air exposure, the muscle free glutamate contents increased markedly (P<0.05) and were significantly higher than the control values (P<0.05). The muscle free alanine contents remained a constant values during the first 12 h of aerial exposure (P>0.05), thereafter, this concentrations increased significantly till the end of experiment (P<0.05). Our results showed that glutamate and NH4+ would be used to synthesize glutamine via glutamine synthetase to convert internal ammonia into non-toxic glutamine in P. dabryanus during air exposure. Furthermore, the P. dabryanus could catabolize several certain amino acids leading alanine form to reduce endogenous ammonia production. The decrease of tissue free glutamate, arginine and proline in P. dabryanus indicated these certain amino acids should be the starting substrate converted to alanine and energy.